Insulin ameliorates dim blue light at night-induced apoptosis in hippocampal neurons via the IR/IRS1/AKT/GSK3β/β-catenin signaling pathway - Qi Liu; Zixu Wang; Jing Cao; Yulan Dong; Yaoxing Chen (Ecotoxicology and Environmental Safety, 2023)
In recent years, the damaging effects of night light pollution, one of the environmental pollutions, on memory has been attracting attention. However, the underlying molecular mechanisms by which light at night, especially blue light at night, impairs memory remains unclear. Here, a total of 42 C57BL6/J mice that exposed to no light at night, dim white light at night (dLAN-WL), or dim blue light at night (dLAN-BL) for 28 days. Behavioral data indicated that exposure to dLAN-BL resulted in severe recognition memory impairment, as evidenced by the reduced recognition index and discrimination index in the novel object recognition test. At the same time, we observed a decrease in plasma insulin levels. Consistent with these changes, we also observed that dLAN-BL reduced the number of neurons in the CA1, CA3 and DG regions of the hippocampus, up-regulated the mRNA expression levels of Bax, down-regulated the mRNA expression levels of Bcl-2, Bcl-xl and the protein expression level of pIRS1, pAKT, pGSK3β, β-catenin in the hippocampus. In vitro experiments, we found that insulin (10 nM) inhibited apoptosis and up-regulated the protein expression levels of pAKT, pGSK3β, β-catenin of HT22 cells induced by H2O2 (200 μM). However, these changes disappeared when the insulin receptors (IR) in HT22 cells were silenced. Taken together, our findings suggested that the impairment of memory in mice induced by dLAN-BL was mediated by insulin via the IR/IRS1/AKT/GSK3β/β-catenin pathway. Data Availability: All data generated or analyzed during this study are included in this published article.